Keterkaitan antara Profitabilitas, Struktur Modal, Ukuran Perusahaan dan Tax Avoidance - Salsa Shalma Auliya; Sofie Yunida Putri (Prosiding Seminar Nasional Ilmu Ekonomi dan Akuntansi, 2026)
This study aims to analyze the interrelationship between profitability, capital structure, firm size, and tax avoidance. It employs a descriptive analysis method combined with a literature review approach. The study draws upon various prior empirical studies indexed in Sinta 2 and Scopus Q2 from the period 2021–2024, as well as relevant secondary data sources. This approach is intended to provide a comprehensive understanding of the factors influencing firms’ propensity to engage in tax avoidance practices. The results of the literature review indicate that there is a relationship between firms’ tendency to engage in tax avoidance and profitability, capital structure, and firm size. Higher profitability leads to increased tax burdens, thereby encouraging management to implement tax planning strategies in an effort to reduce the tax liabilities that must be settled. Furthermore, firms with higher proportions of debt and equity tend to have greater flexibility in managing their financial policies, which may influence their tax strategies. In addition, larger firms typically possess greater resources and broader access to professional expertise, enabling them to better identify and exploit opportunities for tax avoidance in order to maintain cash flow stability. It is expected that this study will contribute theoretically to the development of the literature on taxation and corporate finance. Moreover, the findings are anticipated to serve as a consideration for regulators in formulating more effective tax supervision policies.